2011 IEEE/RSJ International Conference on Intelligent Robots and Systems 2011
DOI: 10.1109/iros.2011.6048282
|View full text |Cite
|
Sign up to set email alerts
|

On active target tracking and cooperative localization for multiple aerial vehicles

Abstract: Abstract-This paper presents a new cooperative active target-tracking strategy for a team of double-integrator aerial vehicles equipped with 3-D range-finding sensors. Our strategy is active because it moves the vehicles along paths that minimize the combined uncertainty about the target's position. We propose a gradient-based control approach that encompasses the three major optimum experimental-design criteria and relies on the Kalman filter for estimation fusion. We derive analytical lower and upper bounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Multi-robot active tracking: In [6], multi-robot trajectories are analytically derived and uncertainty bounds are identified for optimizing the fused estimate of the target position. In [7], a non-convex optimization problem is solved analytically, to minimize the trace of the fused target covariance.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Multi-robot active tracking: In [6], multi-robot trajectories are analytically derived and uncertainty bounds are identified for optimizing the fused estimate of the target position. In [7], a non-convex optimization problem is solved analytically, to minimize the trace of the fused target covariance.…”
Section: State-of-the-artmentioning
confidence: 99%
“…This paper takes its inspiration from [7], [8] and makes several novel contributions. As it is evident from the previous literature review, a large body of research exists on cooperative active target tracking for wheeled robots,butfew works in the literature (cf., [12], [13]) have dealt with UAVs. In addition, oversimplified models (e.g., firstor secondorder integrators) are typically used for the aerial vehicles.…”
Section: B Original Contributions and Organizationmentioning
confidence: 99%
“…the angular velocity for the four propellers). Differently from [13], a discrete-time Kalman filter is used here for fusing the local estimates provided by each aerial vehicle. Under suitable conditions, it is shown that the cost function for the Doptimality criterion that the quadrotors aim at collaboratively reduce, has a single global minimum and no local minima.…”
Section: B Original Contributions and Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several indexes can be used to measure the amount of information, like entropy, mutual information, etc. Most of the works assume Gaussian uncertainties and Kalman (or Information) Filters as the underlying estimation framework, and define utility functions based on these information measures to determine the actuations [12], [13], [14]. However, tracking applications can result in multi-modal distributions when estimating the targets' positions.…”
Section: Introductionmentioning
confidence: 99%